Pars Plana Vitrectomy in Proliferative Diabetic Retinopathy – Retrospective Analysis of Results and Complications - Lemos, José Alberto (2017)
Purpose: To analyze the results and complications of pars plana vitrectomy (PPV) in the treatment of patients with proliferative diabetic retinopathy (PDR). Methods: Retrospective study of all patients that underwent PPV for PDR in the period between April 2012 and June 2014 and with a minimum follow-up of 2 months. Data collected included baseline demographics, best-corrected visual acuity (BCVA), indications for surgery, complications, anatomic and functional success. Results: One hundred and eight eyes of 85 patients underwent PPV for PDR in the referred period. Patient’s mean age was 62.45±10.89 years, with female predominance (55.3%). Mean follow-up time was 12.24 months. Preoperative mean BCVA was 1.37±0.69 logarithm of the minimum angle of resolutions (logMAR). The three main indications for surgery were: vitreous haemorrhage (VH) in 68 eyes, tractional retinal detachment (TRD) in 9 eyes and VH associated with TRD (11 eyes). Fifty-nine eyes underwent phacoemulsification in the same surgery. In the last follow-up appointment, mean BCVA was superior to that registered preoperatively (0.87±0.76 logMAR, p <0.001). Global functional success rate was 80.6%, and it was superior in the HV group (89.7%). Anatomic success rate was 98.1%. Conclusions: Our study suggests PPV can be used successfully to treat PDR complications and often results in patient’s visual acuity improvement.